Phospholamban antisense oligonucleotides improve cardiac function in murine cardiomyopathy - Niels Grote Beverborg (Nature Portfolio, 2021)
Heart failure is a major cause of morbidity and mortality worldwide. Here the authors show that subcutaneous administration of antisense oligonucleotides targeting PLN is an effective strategy in preclinical models of genetic cardiomyopathy and ischemia-driven heart failure.